Transformacija kadrovskega managementa - Bernik, Mojca (2023)
Transformation of Human Resource Management. The scientific monograph Transformation of HRM analyses the areas of HRM that have been exposed to environmental changes in recent years. New approaches and ways of working are being applied in human resources management, arising from the potentional of information technology and changes in the global labor market. The content of the scientific monograph Transformation of HRM analyses the challenges of a long-lived society, which in the field of HRM requires the introduction of changes in the ways of working of older employees. This requires the adaptation of key  job objectives, which involves defining and redefining job descriptions. The present scientific monograph also changes in the functioning of the employe, who, because of the different ways of working, is called a hybrid employee and can be comapred to a ahybrid consumer. The use of modern technologies ha salso brouth abaut changes in the field of education, enabling human resources management of develop smart leatning environmets and thus individualised learning.
Keywords: human resources managemnet; hybrid employessm long-life society; managing older employees; workplace; key goals; smart education; smart pedagogy